Methods and techniques used by the social worker in facing the problems facing those infected with the emerging coronavirus (Covid-19) - Almohammadi, Abdullah Eyadh (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the methods and techniques used by the social worker in facing the problems facing those infected with the emerging coronavirus (Covid-19), as well as to identify the skills used by the social worker in treating problems resulting from infection with the Corona virus, and to identify the most important difficulties facing the social worker in facing the problems that confront the infected, as well as suggestions that help alleviate the problems resulting from infection with the Corona virus. This study belongs to the type of descriptive studies, which relied on the comprehensive social survey method The study population consisted of medical social workers, and their number reached (50) in isolation hospitals in Madinah and Munawwarah. The study reached several results, the most important of which are: One of the most important of these methods and techniques (the use of the method of counseling and guidance for patients to take advantage of the resources available in the community)The results also showed that one of the most important of these skills (the use of the observational skill method to identify the behaviors of the injured), and the results of the study showed that one of the most important of these difficulties (the lack of social workers in the hospital in which I work), and the results of the study also indicated that one of the most important proposals that help in Mitigating the problems resulting from infection with the Corona virus (providing incentives for the specialist for his performance in the medical team).The study recommended the need for cooperation and integration between the institution’s work team and social workers, and for the specialist to find support from the institution’s management and employees, as well as the need to use and experiment with modern therapeutic approaches in social work in general and to serve the individual in particular with people infected with the Corona virus and their families, and training social workers in medical institutions on Practicing the approaches that scientific studies have proven to be effective in facing social pressures resulting from epidemics and emerging diseases.
Keywords: corona virus; pandemic; problem; social worker